Genotype and environment factors driven licorice growth and rhizospheric soil fungal community changes - Han, Tingting; Li, Xianen; Luo, Dan; Ji, Changhao; Chen, Caixia; He, Chao (Frontiers in Microbiology, 2023)
Licorice (Glycyrrhiza uralensis Fisch.) is a widely recognized significant form of medicine in China, with a long-standing history and extensive usage. It is considered the oldest and most prevalent herbal medicine in China. Currently, the licorice market is confronted with the primary challenges of mixed genotypes, inconsistent quality, and inadequate glycyrrhizic acid content. We conducted field experiments to investigate the impact of various cultivation locations on the growth characteristics, active ingredients, rhizospheric soil physicochemical properties and fungal communities of licorice that ten different genotypes. The findings indicated significant variations in these parameters across ten different genotypes of licorice originating from two distinct production regions. The growth characteristics of licorice were primarily influenced by genotype, whereas the active ingredients of licorice were mainly influenced by environmental factors and soil physicochemical properties. Furthermore, the rhizospheric soil physicochemical properties of licorice plants were more influenced by environmental factors than genotypes. Additionally, the distribution of rhizospheric soil fungi in licorice plants of the same genotype exhibited significant variations across different cultivation areas. The utilization of structural equation model synthesis reveals variations in the quantity and strength of pathways that influence the growth characteristics, active ingredients, and rhizospheric soil microbial community of licorice across different cultivation regions. According to its growth characteristics and active ingredients, Z009 proved to be the most suitable genotype for cultivation in Jingtai. From a perspective centered on the active ingredient, Z010 proved to be the most optimal genotype for licorice cultivation in both production areas. Our study aims to enhance the understanding of the ecological adaptability of various genotypes of licorice resources and to identify appropriate licorice genotypes for specific cultivation regions. This research holds significant practical implications for enhancing the yield and quality of licorice, thereby improving its overall development.